Which oral antidiabetic drug to combine with metformin to minimize the risk of hypoglycemia when initiating basal insulin?: A randomized controlled trial of a DPP4 inhibitor versus insulin secretagogues. (June 2016) - Gautier, J.F.; Monguillon, P.; Verier-Mine, O.; Valensi, P.; Fiquet, B.; Dejager, S.; Charbonnel, B.
Highlights: To explore which dual therapy should be maintained when initiating basal insulin in T2DM patients. A dual metformin/DPP4 inhibitor therapy allows achieving a similar efficacy vs. metformin/insulin secretagogues. However it limits the frequency of hypoglycemic episodes. Abstract: We conducted a pilot study to evaluate two therapeutic strategies at the time of insulin initiation in type 2 diabetic patients insufficiently controlled with metformin + insulin-secretagogues (IS, sulfonylureas or glinides). Patients were randomized to remain under the same dual therapy or to receive metformin + DPP4 inhibitors while starting insulin. Similar glycemic control was achieved in both groups. However less hypoglycemia was observed with DPP4 inhibitors despite higher doses of insulin.